“Balance Training Program” Untuk Kader Posbindu Sebagai Upaya Pencegahan Bahaya Jatuh Pada Lansia Yang Tinggal di Area Lahan Basah - Kurnia Rachmawati; Fatma Sayekti Ruffaida; Herawati Herawati (Universitas Lambung Mangkurat, 2023)
Abstract The elderly had a proportion of 14% of the total population in Mandikapau Timur Village, a wetland area. Based on previous assessment, it was found that pain in the musculoskeletal system of the extremities was the most common pain experienced by the elderly (53.5%). Assessment of the risk of falling using the Morse Fall Scale (MFS) showed that most of the elderly (66.7%) have a risk of falling. There were health cadres who run Posbindu, but the knowledge of cadres regarding the health of the elderly was still lacking. Cadre training for fall prevention through increasing musculoskeletal strength in the elderly has never been carried out. Based on the analysis of the situation and problems faced by partners, the solutions offered to solve the problems was a